Animal Functional Magnetic Resonance Imaging: Trends and Path Toward Standardization - Mandino, Francesca; Cerri, Domenic H.; Garin, Clement M.; Straathof, Milou; van Tilborg, Geralda A. F.; Chakravarty, M. Mallar; Dhenain, Marc; Dijkhuizen, Rick M.; Gozzi, Alessandro; Hess, Andreas; Keilholz, Shella D.; Lerch, Jason P.; et al. (Frontiers in Neuroinformatics, 2020)
Animal whole brain functional magnetic resonance imaging (fMRI) provides a non-invasive window into brain activity. A collection of associated methods aims to replicate observations made in humans and to identify the mechanisms underlying the distributed neuronal activity in the healthy and disordered brain. Animal fMRI studies have developed rapidly over the past years, fueled by development of resting-state fMRI connectivity and genetically-encoded neuromodulatory tools. Yet, comparisons between sites remain hampered by lack of standardization. Recently, we highlighted that mouse resting-state functional connectivity converges across centres, although large discrepancies in sensitivity and specificity remained. Here, we explore past and present trends within the animal fMRI community and highlight critical aspects in study design, data acquisition, and post-processing operations, that may affect the results and influence the comparability between studies. We also suggest practices aimed to promote the adoption of standards within the community and improve between-lab reproducibility. The implementation of standardized animal neuroimaging protocols will facilitate animal population imaging efforts as well as meta-analysis and replications studies, the gold standards in evidence-based science.